Effects of Low-Fat Diet, Calorie Restriction, and Running on Lipoprotein Subfraction Concentrations in Moderately Overweight Men - Williams, Paul T. (1994)
We studied the effects of exercise (primarily running), calorie restriction (dieting), and a low-fat, high-carbohydrate diet on changes in lipoprotein subfractions in moderately overweight men in a randomized controlled clinical trial. After 1 year, complete data were obtained for 39 men assigned to lose weight through dieting without exercise, 37 men assigned to lose weight through dieting with exercise (primarily running), and 40 nondieting sedentary controls. We instructed both diet groups to consume no more than 30% total fat, 10% saturated fat, and 300 mg/d of cholesterol, and at least 55% carbohydrates, and the controls were instructed to maintain their usual food choices. Analytic ultracentrifugation was used to measure changes in plasma lipoprotein mass concentrations. In addition, the absorbance of protein-stained polyacrylamide gradient gels was used as an index of concentrations for five high-density lipoprotein (HDL) subclasses that have been identified by their particle sizes, ie, HDL(3c), (7.2 to 7.8 nm), HDL(3b) (7.8 to 8.2 nm), HDL(3a) (8.2 to 8.8 nm), HDL(2a) (8.8 to 9.7 nm), and HDL(2b) (9.7 to 12 nm). Relative to controls, weight decreased significantly in men who dieted with exercise (net difference ± SE, −3.3 ± 0.4 kg/m(2)) and in men who dieted without exercise (−2.0 ± 0.4 kg/m(2)). Dieting with exercise significantly decreased very-low-density lipoprotein (VLDL)-mass concentrations and significantly increased plasma HDL(2)-mass, HDL(3a), HDL(2a), and HDL(2b) relative to both control and dieting without exercise. There were no significant changes in lipoprotein mass and HDL protein for dieters who did not run. Adjustment for weight loss by analysis of covariance eliminated the significant decrease in VLDL-mass and increases in HDL(2)-mass and HDL(2b) in men who both increased exercise and dieted. Thus, the addition of exercise to dieting appears to increase HDL(2)-mass and HDL(2b) through metabolic processes associated with weight loss, and to increase HDL(2a) and HDL(3a) through processes that are independent of weight loss. Previous exercise studies that report changes in HDL that are independent of weight loss may be measuring increases in HDL(2a) and HDL(3a) rather than HDL(2b).